Sustainable resilience in flood-prone rice farming: adaptive strategies and risk-sharing around Tempe Lake, Indonesia - Amandaria, Riri; Darma, Rahim; Zain, Majdah M.; Fudjaja, Letty; Wahda, Muhammad Aksha; Kamarulzaman, Nitty Hirawaty; Bakheet Ali, Hamed; Akzar, Rida (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Recurrent flooding near Tempe Lake, Indonesia, exacerbated by climate change, presents significant challenges for rice-farming communities, threatening their livelihoods and food security. This study explores the adaptive strategies employed by farmers to mitigate flood-related risks and evaluates the role of institutional frameworks in risk-sharing mechanisms. Using a mixed-methods approach, we analysed primary survey data from 140 rice farmers and conducted interviews with irrigation pump operators. The study viewed 30 years of historical flood records to identify environmental patterns affecting agricultural practices. The findings indicate that farmers employ various adaptation strategies to enhance resilience, including irrigation technologies, risk-sharing agreements, and livelihood diversification. Informal co-operative structures play a crucial role, with landowners covering 50% of production costs and farmers receiving 60% of profits after deducting operational expenses. However, flood-related income disruptions and shifting environmental conditions threaten long-term sustainability. This study emphasizes the need to formalize risk-sharing agreements, promote flood-resistant crop adoption, and improve water management infrastructure to address these challenges. Additionally, policies should support the development of community-led co-operative models and flexible contract structures, as well as training and access credit to ensure fair compensation for climate-induced losses. Integrating institutional support, technological advancements, and community-driven adaptation strategies can enhance economic stability, strengthen food security, and ensure the long-term viability of rice farming in flood-prone regions.